Population genomics and antimicrobial resistance dynamics of Escherichia coli in wastewater and river environments - Jose F. Delgado-Blas (Nature Portfolio, 2021)
Jose F. Delgado-Blas et al. report a genomic analysis of two antimicrobial-resistant E. coli populations from wastewater and river water. They find that bacteria from wastewater are more resistant to antibiotics and rely on a diverse set of plasmids for adaptation, while river bacteria adapt mainly via chromosomal changes.